Magnetization and superparamagnetic behavior of FeCu nanoalloys at room temperature via synthesis and simulation - Maryam Bahrami; Mehrangiz Bahrami; S. Jafar Hoseini; Mohammad Hadi Ghatee (Scientific Reports)
Abstract Bimetallic nanoalloys combining magnetic and noble metals are promising for magnetic sensors, catalysis, optical detection, and biomedical imaging applications. Their development relies on understanding morphology, electronic structure, and crystallography. This study explores iron-based magnetic nanoalloys using efficient synthesis and advanced characterization. Molecular dynamics (MD) simulations examined atomic-scale morphology and structural features, linking them to magnetic behavior. A spin-lattice dynamics algorithm simulated iron–copper (FeCu) nanoalloys of varying sizes and compositions. FeCu nanoalloys were synthesized via a one-step reduction reaction and analyzed using multiple techniques, yielding nanoparticles with high saturation magnetization and an 11 nm average size. Simulations and experiments confirmed core-shell (CS) and Janus morphologies, where copper shells an iron core. Findings suggest that composition, rather than morphology alone, predominantly influences magnetic properties, while the core-shell morphology enhances oxidation resistance due to the noble copper metal employed. This study is the first to integrate the spin-lattice algorithm with experimental analysis, providing consistent insights into design and accurate characterization. Thus, it confirms the practical and novel synthesis of low-size FeCu nanoparticles with ideal superparamagnetic properties—exhibiting no hysteresis—suitable for various research and industrial applications.